2019
DOI: 10.1103/physrevb.99.064202
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory description of random Cu-Au alloys

Abstract: Density functional alloy theory is used to accurately describe the three core effects controlling the thermodynamics of random Cu-Au alloys. These three core effects are exchange correlation (XC), local lattice relaxations (LLRs), and short-range order (SRO). Within the real-space grid-based projector augmented-wave (GPAW) method based on density functional theory (DFT), we adopt the quasinonuniform XC approximation (QNA), and take into account the LLR and the SRO effects. Our approach allows us to study the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…Sampling of the possible atomistic configurations of the alloy surface with multiple surface models is one way to treat these systems. 154,155 An important factor to consider with all alloy models is the possibility of adsorbate-induced surface segregation. 156−158 If an adsorbate binds stronger to certain elements, this may provide a driving force for the more strongly binding elements to segregate to the surface.…”
Section: Catalyst Models For Large Nanoparticles and Small Nanoclustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling of the possible atomistic configurations of the alloy surface with multiple surface models is one way to treat these systems. 154,155 An important factor to consider with all alloy models is the possibility of adsorbate-induced surface segregation. 156−158 If an adsorbate binds stronger to certain elements, this may provide a driving force for the more strongly binding elements to segregate to the surface.…”
Section: Catalyst Models For Large Nanoparticles and Small Nanoclustersmentioning
confidence: 99%
“…Although it is easy to create a slab with random atomic configurations, a truly random distribution cannot be achieved with reasonable unit cell sizes because of periodic boundary conditions. Sampling of the possible atomistic configurations of the alloy surface with multiple surface models is one way to treat these systems. , …”
Section: Recent Advances Toward Better Atomistic Models For Heterogen...mentioning
confidence: 99%
“…Based on the studies published previously in the literature, one can emphasize that for Au-Cu alloys with tunable structures and their compositions and properties there are many experimental studies [35][36][37][38], as well as theoretical ones [26,33,34,[39][40][41][42][43][44]. Recent experimental studies have shown that the Au:Cu mass ratio is one of the most important factors affecting the photocatalytic properties, namely the best photocatalytic activity that is found for the Au-Cu alloys with Au:Cu mass ratio equal to 1:1 [38].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies have shown that the Au:Cu mass ratio is one of the most important factors affecting the photocatalytic properties, namely the best photocatalytic activity that is found for the Au-Cu alloys with Au:Cu mass ratio equal to 1:1 [38]. The theoretical studies on Au-Cu alloy can be performed using molecular dynamics [26,33,45], first-principle theory [39,[41][42][43][44], and Monte Carlo simulation [27]. Most of these studies concentrate on Au-Cu nanoparticles or clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Using Cd or Zn as the cation, there is a systematic variation in properties from oxides (CdO, ZnO) to sulfides (CdS, ZnS) to selenides (CdSe, ZnSe) to tellurides (CdTe, ZnTe), but further tuning is available if O/S/Se/Te are mixed with one another at the anion site and Cd/Zn, or indeed other 2+ oxidation state elements, are mixed at the cation site [11][12][13][14][15][16]. In addition to the composition itself, the ordering of ions in an alloy will also affect the properties and deserves consideration [17,18].…”
Section: Introductionmentioning
confidence: 99%